In vitro follicle culture in the context of IVF. Issue 1 (July 2018) - Herta, Anamaria C; Lolicato, Francesca; Smitz, Johan E J
Abstract : The currently available assisted reproduction techniques for fertility preservation (i.e. in vitro maturation (IVM) and in vitro fertilization) are insufficient as stand-alone procedures as only few reproductive cells can be conserved with these techniques. Oocytes in primordial follicles are well suited to survive the cryopreservation procedure and of use as valuable starting material for fertilization, on the condition that these could be grown up to fully matured oocytes. Our understanding of the biological mechanisms directing primordial follicle activation has increased over the last years and this knowledge has paved the way toward clinical applications. New multistep in vitro systems are making use of purified precursor cells and extracellular matrix components and by applying bio-printing technologies, an adequate follicular niche can be built. IVM of human oocytes is clinically applied in patients with polycystic ovary/polycystic ovary syndrome; related knowhow could become useful for fertility preservation and for patients with maturation failure and follicle-stimulating hormone resistance. The expectations from the research on human ovarian tissue and immature oocytes cultures, in combination with the improved vitrification methods, are high as these technologies can offer realistic potential for fertility preservation.